Effects of dexmedetomidine combined with intravenous general anesthesia on hemodynamics and inflammatory factors in patients undergoing laparoscopic colorectal cancer surgery - Chunling Liu; Yong Gui; Min Zeng; Zhidong Zhou (Videosurgery and Other Miniinvasive Techniques)
Introduction: Surgery is the principal treatment option for early colorectal cancer (CRC). Anesthesia plays a crucial role in any surgery as it allows for a painless procedure. Dexmedetomidine is a local anesthetic that reduces pain and discomfort during surgery.